PERBANDINGAN PERHITUNGAN PREMI ASURANSI JIWA BERJANGKA, SEUMUR HIDUP, DAN DWIGUNA PADA KASUS LAKI-LAKI DAN PEREMPUAN - Ahmad Jamiluddin Fikri; Ajeng Afifah Muhartini; Oman Sharoni; Tanti Febrianti; Isnaini Mahuda (LPPM Universitas Bina Bangsa, 2022)
Life insurance is insurance that handles the risks that occur in human life. Insurance company as a handler where the insurance company will pay a certain amount of money in case of death risk to the insurance policyholder. There are two types of premiums, namely net premiums and gross premiums. The premium to be calculated is a single premium. Premium payments on life insurance in the same time, lifetime and bi-use in this study are payments made at once or can be called a single premium. Based on the example of the case of prebandan term life insurance premiums, life insurance for life and bipurpose life insurance between men and women. The value of a single premium of life insurance as long as life has a lower pemi niai and the single lai pemi of bipurpose life insurance has a higher pemi value